2020
DOI: 10.6007/ijarbss/v10-i3/7092
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Child Relationship and Education on Sexuality

Abstract: Mother-child relationship is an important relationship in family, and it is providing a base for children to expand the relationship with others. Through the development of child, adolescences period is a critical development which is regularly understood as the years between the beginning of puberty and the initiation of social independence. Adolescence is a time where by experiencing pubertal changes, brain structures and sexual interest and to understand on their changes, it will be help through education. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Interestingly, parents and partners had surfaced as sources of information. Effective parent-child communication has the bene ts of a delayed of child's rst sexual debut, increased uptake of contraceptives, prevention of STI, HIV/AIDS and adoption of healthy sexual behaviors (Faudzi et al, 2020;Naftaly & Greenley, 2019). The study has revealed that the culture of parents shying away from discussing sexual and reproductive health matters openly is fading.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, parents and partners had surfaced as sources of information. Effective parent-child communication has the bene ts of a delayed of child's rst sexual debut, increased uptake of contraceptives, prevention of STI, HIV/AIDS and adoption of healthy sexual behaviors (Faudzi et al, 2020;Naftaly & Greenley, 2019). The study has revealed that the culture of parents shying away from discussing sexual and reproductive health matters openly is fading.…”
Section: Discussionmentioning
confidence: 99%
“…This means, having a strong relationship with children, as parents, it can help nurture them as they grow from an infant all the way to adulthood. This relationship underpins the development of children's personality, the choices they make throughout life, and much more (Faudzi, Sumari & Nor, 2020). This shows that with appropriate parenting style, parents can help boost the academic performance of their learners through the development and nurturing of appropriate study habits.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Assertions by most researchers (Faudzi et al, 2020;Idris et al, 2020;Jafari et al, 2019;Wunnia, 2017) suggest that the child's relationship with his or her family members at home can influence his or her performance in school. That apart, children in modern societies spend more time in school and for that matter the school environment needs to be made conducive to promote learning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation